Reprogramming The Endocannabinoid System With Emerging Therapeutic Targets For Smart Analgesia - A Comprehensive Review (International Journal of Environmental Sciences, 2025)
Neuropathic pain, a relentless and elusive clinical adversary, continues to defy the efficacy of traditional analgesics. Amid this therapeutic impasse, the endocannabinoid system (ECS) emerges as a dynamic neuroimmune symphony conductor in modulating pain signalling with intricate precision. This review ventures into the molecular corridors of the ECS, spotlighting CB1 and CB2 receptors, FAAH, MAGL, anandamide uptake systems, and sigma-1 receptors as molecular sentinels guarding the gateways of nociception. Among them, CB2 receptor activation and FAAH inhibition unveil a compelling, non-euphoric route to pain suppression, offering analgesia untethered from the psychoactive shadow of CB1. Furthermore, hybrid strategies involving imidazoline I2 receptors and voltage-gated ion channels form a pharmacological mosaic that synergistically silences aberrant pain pathways. With a blend of receptor finesse and enzymatic modulation, the ECS paves a novel therapeutic frontier, one where chronic pain is not merely managed but molecularly outmanoeuvred.